Three Essays on Human Capital (2018)
This PhD dissertation comprises three papers. The first paper analyses the effects of a sudden disease outbreak on human capital outcomes. It studies the causal impact of an unexpected dengue epidemic that occurred in Colombia in 2010 on the national Saber 11 test scores. The results from a difference-in-differences design indicate that the dengue outbreak reduced the average test scores of the 2011-2013 period. The second paper studies the effect of carrying an atypical name on students’ test scores, using a unique dataset for Antioquia, Colombia — “Olimpiadas del Conocimiento” test—. Following an education production function approach, the results suggest that bearing atypical names decrease students’ test scores, although this is true only for boys and for students from full-day institutions. Finally, the third paper analyzes the effect on wages of the cultural distance, in terms of work-related values, between Sweden and the country of birth of the parents of the second-generation immigrants. It uses a unique Swedish longitudinal database of the population born in 1974 and their labor market outcomes between 1996 and 2006. As a proxy of the work-related values of a country, this paper proposes a cultural distance index based on the six Geert Hofstede cultural dimensions. Compared with natives with parents of non-immigrant origin, second-generation immigrants earn less when having a culturally-distant background. Being a woman, working in the public sector, having a higher education degree, having a Swedish mother or father, time, or having a culturally-closer background weakens or even eliminates this negative impact.